DESKRIPSI PERWUJUDAN HIDUP PERSAUDARAAN MUDA-MUDI FRANSISKAN (MUDIFRA) SAN PIO MELA BERDASARKAN SPIRITUALITAS SANTO FRANSISKUS DARI ASISI - Tamba, Henny Yuni Ceta Pebronia; Wulung, FX Heryatno Wono (Bahasa Indonesia, 2023)
Mudifra is a community of the Catholic youth living the Gospel according to spirituality of universal brotherhood Francis of Assisi. He respects God's creatures as brothers. Francis taught that brotherhood isn't only with humans, but also with animals, plants, and other creatures. As followers of Francis, youth are expected to emulate the universal fraternity of Francis. Therefore, the writer is interested in knowing the manifestation of the fraternity of the Franciscan youth group of San Pio Mela which imitates the spirit of the fraternity of Francis. The main problem of this paper is how to strive for the realization of youth fraternity life based on the spirituality of Francis, which includes brothers in the faith, brothers and sisters of different faiths, the poor, and the natural environment. To examine the subject matter, the authors conducted interviews to obtain data and validate its truth. The results of the study show the youth group has been able to establish brotherhood in all of creation fairly well. However, the brotherhood of youth groups with brothers of different faiths and poor relatives who're excluded isn't very visible because there're very few activities related to this. But they realize the brotherhood through their respective experiences.